PENGARUH KEPUASAN GAJI TERHADAP TURNOVER INTENTION DENGAN KOMITMEN ORGANISASIONAL SEBAGAI PEMEDIASI PADA KARYAWAN KOPERASI SIMPAN PINJAM ARTHA MUSTIKA WONOSEGORO KABUPATEN BOYOLALI - Sutarno, Steva Noviolanda, Suprayitno & (Universitas Slamet Riyadi, 2017)
The turnover rate of employees at Credit Unions Artha Mustika WonosegoroBoyolali district is currently very high. The purpose of this study was to analyze thesignificance of the effect on pay satisfaction and organizational commitment onemployee turnover intentions. Analyze the significance of the influence of organizationalcommitment on employee turnover intentions. Analyze significant effect on turnoverintentions salary satisfaction with organizational commitment as a mediating variable.This study uses survey method, the type of data used quantitative and qualitative data,the data source used primary data and secondary data. Population and sample in thisstudy were all employees of Credit Unions Artha Mustika Wonosegoro Boyolali totaling32 employees, so this study is a census study. Data collection methods are used:questionnaires and documentation. Data analysis technique used to test the validity,reliability test, classic assumption test, and path analysis. In conclusion, that there is asignificant impact salary satisfaction to organizational commitment. There is significantinfluence pay satisfaction and organizational commitment to turnover intentions. Theresults of the analysis we concluded that the mediating effect of organizationalcommitment mediates not pay satisfaction influence on turnover intentions.Keywords: pay satisfaction, organizational commitment, turnover intentions.